Emerging technologies for genetic modification of solventogenic clostridia: From tool to strategy development. (August 2021) - Bai, Sheng-Kai; Hong, Ying; Wu, Yi-Rui
Highlights: Genetic tools for metabolic engineering solventogenic clostridia are summarized. Advantages of the genetic modification tools are compared and emphasized. Strategies and insights involved in clostridial strain engineering are demonstrated. Challenges and trends for future engineered microbial biorefinery are discussed. Abstract: Solventogenic clostridia has been considered as one of the most potential microbial cell factories for biofuel production in the biorefinery industry. However, the inherent shortcomings of clostridia strains such as low productivity, by-products formation and toxic tolerance still strongly restrict the large-scale application. Therefore, concerns regarding the genetic modification of solventogenic clostridia have spurred interests into the development of modern gene-editing tools. In this review, we summarize the latest advances of genetic tools involved in modifying solventogenic clostridia. Following a systematic comparison on their respective characteristics, we then review the corresponding strategies for overcoming the obstacles to the enhanced production. Discussing the progress of other microbial cell factories for solventogenesis, we finally describe the key challenges and trends with valuable recommendations for future large-scale biosolvent industrial application.